Freezing of Oocytes and Its Effect on the Displacement of the Meiotic Spindle: Short Communication - János Konc; Katalin Kanyo; Rita Kriston; József Zeke; Sándor Cseh (The Scientific World Journal)
Our investigations focused on spindle dynamics/displacement in frozen-thawed human oocytes. In each oocyte, prior to freezing and after thawing and culturing, the presence/location of the spindle was determined with the Polscope technique. A total of 259 oocytes have been thawed with a survival rate of 81.1%. From the 210 survived oocytes, 165 were fertilized (78.6%) and 89.1% of them cleaved. A total of 143 embryos were transferred into 63 patients resulting in 11 clinical pregnancies (17.5%), 7 of which resulted in live birth of 8 babies (1 twin pregnancy). We were able to detect the spindle in 221 of 259 oocytes (85.3%). After thawing and culturing the oocytes, we were able to visualize the spindle in 177 of 210 oocytes (84.3%). In 83 of these 177 oocytes, the spindle was observed to be in the same location as it was before cryopreservation (46.9%). However, in 94 of these 177 oocytes (53.1%), the spindle reformed in a different position/location relative to the polar body. Our results show that after thawing and culture in half of the spindle-positive oocytes the spindle was detected in a new location, indicating that the spindle and the polar body move relative to each other.